Effect of explosive mixture on quality of explosive welds of copper to aluminium. (5th April 2016) - Loureiro, A.; Mendes, R.; Ribeiro, J.B.; Leal, R.M.; Galvão, I.
Abstract: The aim of this research is to investigate the influence of explosive ratio and type of sensitizer on the quality of explosive welds between copper and aluminium alloy plates. The welds were performed on a partially overlapping joint configuration using an emulsion explosive (EE) with two different sensitizers, hollow glass microspheres (HGMS) and expanded polystyrene spheres (EPS). Welds with an improved surface were achieved by using the HGMS sensitizer. A higher wave amplitude was registered in welds produced with the EPS sensitizer. In turn, the dimension of the molten pockets was influenced by the explosive ratio, increasing in size with increases in the values of this parameter. The intermetallic content of these zones varied according to the sensitizer type. Unlike the CuAl2 phase, the Cu-richer phases CuAl and Cu9 Al4 were only identified in welds performed using the EPS sensitizer. An increase in hardness was observed at the interface of all welds, which resulted from both the presence of intermetallic phases and the plastic deformation of the materials promoted by the impact. This effect was most evident on the aluminium alloy side. All the welds had a greater strength than copper, i.e. the weakest material of the joint. Graphical abstract: Highlights: Welds produced with hollow-glass microspheres sensitizer display better surface than welds done with expanded polystyrene Wave amplitude and molten pockets increase by using expanded polystyrene sensitizer and higher explosive ratio respectively The molten pockets are predominantly composed of brittle Al-Cu intermetallic phases Intermetallics of higher copper content are formed in molten pockets of welds done with expanded polystyrene sensitizer The formation of intermetallic phases does not impair the tensile-shear strength of the interface bond